Immunotherapy and Gene Therapy: New Challenges in the Diagnosis and Management of Drug-Induced Liver Injury - Delire, Bénédicte; De Martin, Eleonora; Meunier, Lucy; Larrey, Dominique; Horsmans, Yves (Frontiers in Pharmacology, 2022)
In the last five years, the landscape of oncologic treatments has been deeply modified with the development and use of immune checkpoint inhibitors (ICIs) that exert their anti-tumoral effect by reverting the exhausted phenotype of tumor-infiltrating lymphocytes. This innovative therapeutic strategy has widely changed the prognosis of some advanced neoplastic diseases such as melanoma and lung cancer, providing durable remission for a significant number of patients. Unfortunately, immune-related adverse events (irAEs), especially ICIs-induced hepatitis, may be in some cases very severe, impairing the prognosis of the patient. Guidelines available today on the diagnosis and management of ICIs-induced hepatitis are mainly based on expert opinions and case series. This lack of large data is explained not only by the low incidence of hepatic adverse events but also by their clinical heterogeneity and variable severity. In this paper, we will review the clinical, biological and histological characteristics of ICIs-induced liver injury. We will discuss the current knowledge on their pathological mechanisms and their therapeutic strategy based on immunosuppressive treatment for the more severe cases. Regarding severity assessment, we will discuss the gap between the oncologist and the hepatologist’s point of view, highlighting the need for multi-disciplinary management. While initially developed for notably less frequent diseases than neoplastic ones, gene therapy is going to be a revolution for the treatment of diseases not responding to pharmacological therapy. Limited but growing data describe liver injury after the administration of such therapy whose exact physiopathology remains unknown. In this paper, we will discuss the available data supporting the role of gene therapies in the onset of drug-induced liver injury and related mechanisms. We will describe the clinical context, the biological and histological features and the management currently proposed.